Tennis vs padel: Precompetitive anxiety as a function of gender and competitive level - Rodríguez-Cayetano, Alberto; Hernández-Merchán, Félix; Manuel De Mena-Ramos, José; Sánchez-Muñoz, Antonio; Pérez-Muñoz, Salvador (Frontiers in Psychology, 2022)
The main objective of this research is to analyze the level of anxiety and precompetitive self-confidence of tennis and padel players and to check the influence of gender and competitive level in each of the sports. Four hundred and twenty-three tennis and padel players, with a mean age of 15.40 (± 3.43) years, participated in the study. Of the total number of players surveyed, 291 were padel players and 132 were tennis players. The Spanish version of the Competitive State Anxiety Inventory-2R (CSAI-2R) in the Spanish version was used to measure the level of cognitive anxiety, somatic anxiety and self-confidence between 30 and 35 min before the start of the match. The general results showed that the level of self-confidence of padel players is higher of tennis players. In relation to gender, female tennis players showed a higher level of precompetitive anxiety than male players, while, in padel, it was the opposite. In terms of competitive level, U14 players had the highest level of self-confidence and the lowest level of precompetitive anxiety. When comparing both sports, female tennis players show a higher level of state-anxiety than female padel players and U14 tennis players are the ones who showed a higher level of self-confidence. This study shows how precompetitive anxiety is one of the most important psychological variables in relation to sport performance and how it can vary according to gender and competitive level.